(untitled) (American Journal of Research in Humanities and Social Sciences, 2022)
This research(Returning to the Origin of Judgment in the Corona Pandemic) is one of the important researches that dealt with jurisprudential rulings related to epidemics and pandemics, in which the researcher spoke about the Corona pandemic. The researcher also discussed how to deal with it through legal rulings, and how to return to the origin of the ruling after the end of this pandemic. It dealt with the definition of the origin, and the rule for the fundamentalists, and the definition of the pandemic, and the Corona pandemic. It then proceeded to mention the jurisprudential rulings related to prayer, fasting, and pilgrimage, and how to refer to them to the origin of the ruling after the demise of the permission. The research concluded with the most important findings.